2010
DOI: 10.1099/mic.0.039719-0
|View full text |Cite
|
Sign up to set email alerts
|

Selenite-induced cell death in Saccharomyces cerevisiae: protective role of glutaredoxins

Abstract: Unlike in higher organisms, selenium is not essential for growth in Saccharomyces cerevisiae. In this species, it causes toxic effects at high concentrations. In the present study, we show that when supplied as selenite to yeast cultures growing under fermentative metabolism, its effects can be dissected into two death phases. From the time of initial treatment, it causes loss of membrane integrity and genotoxicity. Both effects occur at higher levels in mutants lacking Grx1p and Grx2p than in wild-type cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 63 publications
1
48
1
Order By: Relevance
“…It has been reported that yeasts are hypersensitive to sodium selenite; high concentrations of Se lead to DNA damage when the cells are growing in the exponential phase (Izquierdo et al, 2010). Studying different sodium selenite concentration, we did not observe an inhibition of K. marxianus growth.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been reported that yeasts are hypersensitive to sodium selenite; high concentrations of Se lead to DNA damage when the cells are growing in the exponential phase (Izquierdo et al, 2010). Studying different sodium selenite concentration, we did not observe an inhibition of K. marxianus growth.…”
Section: Discussioncontrasting
confidence: 58%
“…GSH) to reduce selenite to elemental selenium by an intrinsic detoxification mechanism (Izquierdo et al 2010). Elemental selenium can be generated by the Painter-type reactions of selenite with reduced glutathione (Zannoni et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Global glutathionylation patterns have interestingly revealed that S. cerevisiae mutants lacking Grx1p and Grx2p do not have high levels of protein glutathionylation, while a mutant lacking the cytosolic TRXs, Trx1p and Trx2p constitutively display protein hyperglutathionylation (Greetham et al, 2010). One possible explanation for the higher Ca 2+ signals and increased glutathionylation in the grx1Δ strain is the high oxidizing conditions in the cells, since Grx1p has been shown to play a role in protection against oxidative stress (Izquierdo et al, 2010;Luikenhuis et al, 1998). Ca 2+ flux into the cytoplasm of the yeast S. cerevisiae is tightly controlled by the opening and closing of two channels: the vacuolar channel Yvc1p and the plasma membrane channel whose principal subunit is Cch1p.…”
Section: Discussionmentioning
confidence: 99%